Introducing LIVA to measure long‐term firm performance - Wibbens, Phebo D.; Siggelkow, Nicolaj (Strategic Management Journal, 2020)
ABSTRACT Research summary This article introduces a new measure of long‐term firm performance: long‐term investor value appropriation (LIVA). This measure helps to address a disconnect between the common theoretical assumption that managers optimize firm value, and the widespread empirical practice of measuring performance using short‐term ratios such as return on assets (ROA). LIVA can lead to markedly different strategic insights compared to commonly used measures such as ROA and cumulative abnormal returns. For instance, the widely cited finding of a U‐shaped relation between acquisition experience and performance turns out to be largely driven by short‐term stock price movements and vanishes when using 10‐year LIVA. Managerial summary Managers have a large number of performance measures at their disposal, such as return on assets, total shareholder returns, and earnings before interest and taxes. However, these short‐term measures do not capture well whether a firm creates long‐term shareholder value, which is one of the primary objectives for most firms. Addressing that gap, this article introduces a new measure called long‐term investor value appropriation (LIVA). LIVA can be constructed using publicly available stock market data and it can help managers to better analyze historical long‐term performance.